2018
DOI: 10.1016/j.atherosclerosis.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Decreased iron stores are associated with cardiovascular disease in patients with type 2 diabetes both cross-sectionally and longitudinally

Abstract: Low iron status was associated with CVD risk in T2D. This pattern was consistent in populations at different cardiovascular risk. Low iron status seems to be harmful for cardiovascular health in T2D and it may be a target for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The disruption of iron homeostasis can guide tissue iron overload, which has been proven to contribute to the generation of ROS and oxidative stress [9]. Body iron stores, expressed as serum ferritin, have been proposed to be a contributor of atherosclerosis [16], although the epidemiological association is yet to be fully understood [20,21]. The confirmation for this hypothesis is that high serum ferritin levels are associated with oxidative stress, an event implicated in lipoprotein oxidation [9], such as oxLDL [16], Figure 2 shows a diagram that summarizes the possible relationship between oxLDL ferritin-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disruption of iron homeostasis can guide tissue iron overload, which has been proven to contribute to the generation of ROS and oxidative stress [9]. Body iron stores, expressed as serum ferritin, have been proposed to be a contributor of atherosclerosis [16], although the epidemiological association is yet to be fully understood [20,21]. The confirmation for this hypothesis is that high serum ferritin levels are associated with oxidative stress, an event implicated in lipoprotein oxidation [9], such as oxLDL [16], Figure 2 shows a diagram that summarizes the possible relationship between oxLDL ferritin-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most prior studies were conducted between US and European populations [8,10,14,22,23,25]. There is little evidence in Asian populations [11,12,16,21], and there is scarce information regarding iron metabolism on Mexican and South American populations [26]. Caucasians and Asians have been shown to maintain different serum ferritin levels, suggesting a possible difference in the homeostasis of ferritin between populations [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…While ferritin levels greater than 1000 ng/mL in serum was described as an overall marker for diseases [44], levels lower than 30 ng/mL were postulated to be an indicator for iron deficiency [45]. Decreased serum ferritin levels were also correlated with a higher risk for cardiovascular diseases in patients with type 2 diabetes [46].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent large sample study from UK shown that low iron status was associated with CVD risk in T2DM, suggesting that low iron status seems to be harmful for cardiovascular health in T2DM. However, the underlying mechanisms are still unclear [10]. The European Prospective Investigation into Cancer and Nutrition-Potsdam study concluded that high SF levels are associated with high risk of T2DM that is independent of established diabetes risk factors [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis showed that increased ferritin levels were independently and positively associated with the presence of MetS, with an odds ratio of higher than 1.73 [9]. However, a recent large sample study from UK shown that low iron status was associated with CVD risk in T2DM, suggesting that low iron status seems to be harmful for cardiovascular health in T2DM [10].…”
Section: Introductionmentioning
confidence: 99%